Zoo babies! - Husar, Lisa.; Husar, Mike. (Helena, MT : Farcountry Press., 2011)
Simple text and color photographs introduce babies and toddlers to wild animals.
On board pages.
Cover title.
Keywords: Zoo animals; Animals -- Infancy; Animals -- Infancy; Zoo animals; Animals -- Infancy; Zoo animals; Fiction; Juvenile works